A registrar's creed: Simplify, simplify, simplify. Issue 9 (12th October 2020) - Enos, Gary A.
Abstract : Grant McMillan sees the role of a university registrar primarily as one of cutting through red tape, making the institution's pathways to teaching and learning as clear as possible. As Registrar at Trinity Western University in Langley, British Columbia, McMillan organizes his office's everyday operations around the theme "Are we making it easier to get an education?"